(untitled) (GAIMS Journal of Medical Sciences, 2025)
Background: Determining gestational age (GA) significantly influences the prognosis of newborns. Of the various methods available for gestational age assessment, gestational age assessment by first trimester ultrasonography (USG) as the most reliable method gestational and by LMP (last menstrual period), is next best surrogate. In remote areas and rural settings in Low and Middle Income Countries, the reliability of LMP based GA assessment is questionable due to low literacy rates and less awareness among women and USG is not cost effective. In such a scenario, GA assessment by clinical methods like New Ballard Score (NBS) seems an attractive alternative. Hence this study was conducted to compare the reliability of GA assessments by LMP and NBS as compared to 1st trimester ultrasonography in our institute. Methods: This was a prospective study carried out at neonatal intensive care unit of a tertiary care teaching hospital of western Gujarat, India, from August 2022 to July 2023. A total of 200 neonates with mother having first trimester scan and who recalls LMP were recruited for the study. Gestational age according to first trimester scan was calculated and compared with gestational age according to LMP and NBS. Results: Gestational age by UGS with NBS show significant correlation (p value <0.001) Gestational age by LMP with NBS show significant correlation (p value <0.001) Significant correlation was also observed between gestational age accessed by LMP, first trimester USG and NBS (p value <0.001) Gestational age by UGS with NBS which gave a higher correlation (r = 0.886), Correlation among all three gestational age by LMP, USG and NBS which came out to be lower than previous (r =0.545) and at last Correlation amongst gestational age according to LMP and NBS came out to be lowest (r =0.540). Hence, gestational age by USG comes out to be most similar with gestational age by NBS. Conclusions: In low resource settings and in public sector hospitals, GA assessment by NBS is a more reliable option than LMP, and it closely correlates with GA assessed by USG.